SAT0536 Axial alignment of the knee – importance in cartilage repair? high tibial osteotomy vs. distraction. (15th June 2017) - Besselink, N; Heerwaarden, R van; Woude, J van der; Wiegant, K; Spruijt, S; Lafeber, F; Spil, W van; Mastbergen, S
Abstract : Background: Opening-wedge high tibial osteotomy (HTO) is primarily indicated in treating varus gonarthrosis. The rationale behind HTO treatment of knee osteoarthritis (OA) is to unload the affected compartment, this is accomplished by correcting the angular deformity towards the unaffected compartment, i.e. shifting the hip-knee-ankle angle (HKA; mechanical axis) towards varus for a medial lesion. Knee joint distraction (KJD) is an alternative joint-sparing treatment for knee OA and has been demonstrated to decrease pain, improve function, and increase joint space width (JSW) 1 . Objectives: To investigate the importance of axial alignment (and correction) in these two effective (joint-sparing) treatments of medial knee OA. Methods: Patients with medial knee OA, a HKA less than 12° varus, normal knee stability, younger than 65 years, and a BMI less than 35 kg/m 2 were randomized to HTO (n=46) or KJD (n=23). WOMAC and VAS pain were collected at baseline and after twelve months. To assess structural outcome, JSW was measured on knee radiographs, before and after both treatments. HTO patients had full leg standing anteroposterior radiographs taken before and after surgery, KJD patients only had these taken before surgery. Therefore, the femur-tibia angle (FTA; anatomical axis), acquired using Knee Image Data Analysis (KIDA), was investigated as an alternative for assessing axial alignment. Agreement between axial alignment as defined by HKA and by FTA appeared to be fair (ICC=-0.414). WOMAC and VAS Pain were then related to (changes in) axial alignment, Kellgren & Lawrence (K&L) grade, BMI, gender, pre-operative range of motion (ROM), and age as independent variables in linear regression models. Results: Patient baseline characteristics were not statistically significantly different between patients treated with KJD or HTO (see table 1 ). WOMAC increased statistically significantly one year after either treatment (KJD:Δ21.05±19.93; HTO:Δ27.80±15.32; both p<0.001). Likewise, VAS pain decreased (KJD:Δ-23.89±29.67, p=0.001; HTO:Δ-35.42±24.06, p<0.001). KJD led to a statistically significant increase in mean JSW (Δ0.50±0.88mm, p=0.014), and both treatments led to a statistically significant increase in medial (KJD:Δ0.81±1.16mm, p=0.004; HTO:Δ0.47±0.69mm, p<0.000) as well as minimal JSW (KJD:Δ0.85±0.96mm, p<0.000; HTO:Δ0.35±0.51mm, p<0.000) after one year. The FTA changed significantly in the HTO group after one year (Δ0.73 o, p=0.005), while the KJD group showed a trend (Δ0.77 o, p=0.105). In the KJD group, changes in clinical outcomes were not associated with pre-operative HKA, changes in FTA, K&L grade, BMI, gender, pre-operative ROM, or age. In contrast, in the HTO group a significant association was demonstrated for a change in WOMAC with a change in FTA (std.β=-0.341) and for a change in VAS Pain with baseline age (std.β=-0.323), as seen in table 2. Conclusions: Both KJD and HTO lead to a statistically significant clinical and structural benefit after one year. Nevertheless, the change in FTA was associated with WOMAC change after one year in the HTO group, but not in the KJD group. This indicates that axial alignment correction may not per se be necessary for clinical benefit. References: van der Woude et al. Five-Year Follow-up of Knee Joint Distraction. 2016 Cartilage. Disclosure of Interest: None declared